Pathogenicity of Leptospira icterohaemorrhagiae serovar Lai strain Langkawi in guinea pigs (Cavia porcellus) - Hartady, Tyagita; Bahaman, Abdul Rani; Sabri, Jasni; Tengku Ibrahim, Tengku Azmi; Hussein, Fuzina Nor (Veterinary Association Malaysia, 2019)
A tourist was infected with a new strain of leptospires namely, Leptospira icterohemorrhagiae serovar Lai strain Langkawi, when he was on vacation in Langkawi, Malaysia. The leptospiral strain was successfully isolated from the patient in the Netherland. In this study, the bacteria were retrieved from Holland and inoculated into fifteen guinea pigs in Universiti Putra Malaysia (UPM) to determine its pathogenicity. The main clinical symptoms in the guinea pigs were decreased appetite and jaundice. Blood profile showed high neutrophil, lymphocyte, PCV, RBC, haemoglobin, leukocyte and thrombocyte counts. Besides that, enhancement of electrolytes such as sodium (Na), chloride (Cl), and potassium (K) was also noted. Biochemical examination showed an increase alkaline phosphatase (ALP), aspartate transaminase (AST) and bilirubin levels. Albumin, alanine transaminase (ALT), blood urea, total protein and creatinine were low values. Histopathological examination under haematoxylin and eosin staining showed evidence of haemorrhages, congestion and oedema in all organs, with inflammatory cell infiltration characterized by neutrophils, lymphocytes and macrophages. Hydropic degeneration and cell necrosis were also common in the findings. Leptospires were detected from Day 2 p.i by silver staining and transmission electron microscopy (TEM). Rise in antibody titre was seen as early as Day 5 p.i and leptospiral DNA was detected by PCR in the kidneys and liver on Day 3 and Day 5, respectively. The findings were indicative of leptospirosis. This study demonstrated that guinea pigs are a suitable animal model to illustrate the clinical symptoms and pathological changes seen following infection with Leptospira icterohaemorrhagiae serovar Lai strain Langkawi. In general, the symptoms and changes seen in leptospirosis are similar to viral infections and the information and data from this present study would help differentiate infection due to leptospires from that of viral infection. Leptospiral infection has often been misdiagnosed to be viral infection such as influenza and dengue which have similar signs and symptoms as leptospirosis.